MANGROVE BRACHYURAN CRABS IN WORI, NORTH SULAWESI, INDONESIA - Pratiwi, Rianta; Widyastuti, Ernawati (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2018)
The study for faunal diversity from mangrove sites in Wori were very less work carried out, especially on brachyuran crab taxa. Healthy mangrove forests provide a critical for many species of Crabs in intertidal and estuarine areas are keys to healthy marine ecology. Mangroves are the most suitable feeding, breeding and nursery grounds for crabs and other crustaceans. In this study, the habitat distribution and diversity of crabs in Wori mangrove environment was recorded from October 2015 and August 2016. In view of the significance of the mangrove habitat, in present study we selected three station with different habitat specifications as in Wori Seaward (WSW), Wori Middle zone (WMZ) and Wori Landward (WLW). Total 15 species and 307 individuals of brachyuran crabs were recorded belonging to 10 genera and 6 families. Crabs belonging to family Sesarmidae was most dominant with 7 species. The other major outcome of study was maximum diversity was found at Wori Landward (WLW) site with 13 species, followed by Middle Zone (WMZ) site with 11 species and Wori Seaward (WSW) site with 10 species. Keywords: Brachyuran crabs, mangroves, mud flats, estuary, Wori, Bitung, North Sulawesi Indonesia